A clinical case report of Pyoderma gangrenosum - Alfaiate, Teresa (2006)
Pyoderma gangrenosum is a chronic infl ammatory dermatosis, of unknown aetiology,1,2 which presents as painful and rapidly progressive necrotizing and ulcerative skin lesions. It may be associated with other pathologies, such as infl ammatory bowel disease, rheumatoid arthritis, Behçet disease, Wegener’s granulomatosis, active chronic hepatitis, or other blood diseases (multiple myeloma, other monoclonal gammopathies, leukaemia).1,2 However, approximately 50% of the cases arise in isolation.1The authors describe a clinical case who presented with ulcerated lesions in the lower limbs. Despite the absence of respiratory, cardiac, pulmonary or genito-urinary complaints, the initial analytical assessment detected leukocytosis, thrombocytosis, normocytic normochromic anaemia and discrete renal failure. The patient was admitted to clarify the clinical picture and, if possible, to exclude underlying systemic disease.The diagnosis was found to be pyoderma gangrenosum associated with systemic vasculitis, probably Wegener’s granulomatosis.Early haemodialysis was necessary due to rapid and progressive renal dysfunction. Nevertheless, therapy with corticosteroids and immunosuppressants markedly improved skin lesions and renal function was restored.